Bezrobocie absolwentów szkół w Łodzi - Wasiak, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Unemployment is a serious social and economic problem with severe consequences for the entire economy and for individual unemployed and their families.More and more frequently unemployment affects young people. In an effort to find out how high school graduates influence the global structure of unemployment in the Lodz area one could argue that growing unemployment is a side effect of rising education level in ever-increasing number of young people.Education level and qualifications are essential in Polish labour market. More and more companies are looking for prospective employees who are qualified and can start work right away without any additional training. This means that the higher education level and professional qualifications of a prospective employee, the bigger a chance to find and hold down a job. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 178-192